Pengaruh Macam dan Dosis Urine Pada Pertumbuhan dan Hasil Mentimun (Cucumis sativus L) dalam Polibag - Besin, Wendeliana Wati; Sunaryo, Yacobus; Prasetyowati, Sri Endah (JURNAL ILMIAH AGROUST, 2023)
This study aims to determine the effect of giving rabbit and goat urine on the growth and yield of cucumbers in polybags. This research was carried out in the yard of the Rejowinangunan sub-district, Kota Gede sub-district, Yogyakarta city. The research was conducted from June to August 2022. This study used a Ducan’s Multiple Range Test (DMRT), with the first factor being the type of urine, namely: rabbit urine (T1) and goat urine (T2), and the second factor, namely urine dose: control without giving urine, D1 55x5 ml/plant and D2 66x5 ml/plant. Variables observed included plant height, number of leaves, number of branches, fruit length, fruit diameter, fruit weight, and number of fruit. Data analysis used ducan's multiple range test (DMRT). The results of the study stated: 1. At a dose of 66 x 5 ml/plant treatment, goat urine produced long fruit weight, which was higher than rabbit urine. Meanwhile, at a dose of 55 x 5 ml/plant, rabbit urine produced the same fruit length, fruit weight, and fruit diameter as goat urine. 2. Treatment of doses and types of urine did not make a significant difference in the number of leaves, number of branches, and plant height. Meanwhile, the amount of goat urine produced more fruit than rabbit urine. 3. The types of treatments resulted in the number of leaves, number of branches, plant height, number of fruits, fruit diameter and fruit weight which were not significantly different from the control. Meanwhile, in the length of the fruit, the type of treatment produced a longer fruit length than the control